A numerical investigation into the importance of bed permeability on determining flow structures over river dunes. Issue 4 (15th April 2017) - Sinha, Sumit; Hardy, Richard J.; Blois, Gianluca; Best, James L.; Sambrook Smith, Gregory H.
Abstract: Although permeable sediments dominate the majority of natural environments past work concerning bed form dynamics has considered the bed to be impermeable, and has generally neglected flow between the hyporheic zone and boundary layer. Herein, we present results detailing numerically modeled flow which allow the effects of bed permeability on bed form dynamics to be assessed. Simulation of an isolated impermeable bed form over a permeable bed shows that flow is forced into the bed upstream of the dune and returns to the boundary layer at the leeside, in the form of returning jets that generate horseshoe‐shaped vortices. The returning flow significantly influences the leeside flow, modifying the separation zone, lifting the shear layer adjoining the separation zone away from the bed. Simulation of a permeable dune on a permeable bed reveals even greater modifications as the flow through the dune negates the formation of any flow separation in the leeside. With two dunes placed in series the flow over the downstream dune is influenced by the developing boundary layer on the leeside of the upstream dune. For the permeable bed case, the upwelling flow lifts the separated flow from the bed, modifies the shear layer through the coalescence with vortices generated, and causes the shear layer to undulate rather than be parallel to the bed. These results demonstrate the significant effect that bed permeability has on the flow over bed forms that may be critical in affecting the flux of water and nutrients. Key Points: We demonstrate the significant effect that bed permeability has upon the structure of flow over bed forms Over permeable beds flow is forced into the bed upstream of the bed form returning in the leeside as jets of flow Returning flow influences the separation zone lifting the shear layer bounding the separation zone and changing the bed shear stresses